FAKTOR PENYEBAB TERJADINYA AGRESIVITAS SAAT BERTANDING PADA ATLET SEPAKBOLA PEKAN OLAHRAGA PELAJAR DAERAH (POPDA) KAB SUMENEP - Whinata Kardiyanto, Deddy (Jurnal Phederal Penjas, 2014)
This study aimed to determine the occurrence Causes Aggressiveness At Football Athletes Compete In Regional Sports Week (POPDA) Kab Sumenep. This study used a qualitative methodology with a phenomenological approach. The data collected by using observation and semi-structured interviews. Determination of research subjects by using purposive sampling with a reference from your observation. Researchers took four of the 17 athletes that competed POPDA football as a primary Subject and two as secondary subjects, which includes the coach and one player. Data analyzed using an interactive model data reduction, the data display, and verification of conclusions by Miles andHuberman. The results indicate that the factors that caused the aggressiveness of the athletes POPDA Kab Sumenep is the referee's leadership, endangering any bodily contact that makes the aggressiveness of football athletes POPDA uncontrolled Kab Sumenep, any negative utterances spoken by the opponent, and the presence of other aggressive that wish to injure an opponent.